Layers of listening: Qualitative analysis of the impact of early intervention services for first-episode psychosis on carers' experiences. (August 2015) - Lavis, Anna; Lester, Helen; Everard, Linda; Freemantle, Nicholas; Amos, Tim; Fowler, David; Hodgekins, Jo; Jones, Peter; Marshall, Max; Sharma, Vimal; Larsen, John; McCrone, Paul; et al.
Abstract : Background: Early intervention services (EIS) comprise low-stigma, youth-friendly mental health teams for young people undergoing first-episode psychosis (FEP). Engaging with the family of the young person is central to EIS policy and practice. Aims: By analysing carers' accounts of their daily lives and affective challenges during a relative's FEP against the background of wider research into EIS, this paper explores relationships between carers' experiences and EIS. Method: Semi-structured longitudinal interviews with 80 carers of young people with FEP treated through English EIS. Results: Our data suggest that EIS successfully aid carers to support their relatives, particularly through the provision of knowledge about psychosis and medications. However, paradoxical ramifications of these user-focused engagements also emerge; they risk leaving carers' emotions unacknowledged and compounding an existing lack of help-seeking. Conclusions: By focusing on EIS's engagements with carers, this paper draws attention to an urgent broader question: as a continuing emphasis on care outside the clinic space places family members at the heart of the care of those with severe mental illness, we ask: who can, and should, support carers, and in what ways?